Novel molecular markers for inference of phylogenetic relationship and differential detection of Moniliophthora perniciosa AND Moniliophthora roreri - Magalhães, Eduardo Henrique Porto (2021)
Dissertação (mestrado) — Universidade de Brasília, Instituto de Ciências Biológicas, Departamento de Fitopatologia, 2021.